The Margin of Islamic Microfinance Institution: To What Extent Does Capital Structure Matter - Diyah Ariyani (University of Darussalam Gontor, 2021)
The aim of this research is to analyze role of Islamic Microfinance Institution for empowering and developing micro industry. The measurement of the performance institution to stimulate economic growth is NPLSM (Net Profit Los Sharing Margin). This study analyze how is capital structure affect NPLSM (Net Profit Los Sharing Margin) in Indonesia by using multiple linear regression and data panel to see the great NPLSM which is influenced by capital structure. To see how is capital structure influence of margin, using data on period 2010-2016. It is, where the capital structure as the independent variable and the margin as the dependent variable. The result is the capital structure has no effect on the margin.